A Novel True Random Number Generator Based on Mouse Movement and a One-Dimensional Chaotic Map. (2nd February 2012) - Xingyuan, Wang; Xue, Qin; Lin, Teng
Abstract : We propose a novel true random number generator using mouse movement and a one-dimensional chaotic map. We utilize the x -coordinate of the mouse movement to be the length of an iteration segment of our TRNs and the y -coordinate to be the initial value of this iteration segment. And, when it iterates, we perturb the parameter with the real value produced by the TRNG itself. And we find that the TRNG we proposed conquers several flaws of some former mouse-based TRNGs. At last we take experiments and test the randomness of our algorithm with the NIST statistical test suite; results illustrate that our TRNG is suitable to produce true random numbers (TRNs) on universal personal computers (PCs).